Builder of modern India Lal Bahadur Shashtri - "Sharma, Malti" (Delhi, 2015)
Lal Bahadur Shastri was the third (second, and acting, being Gulzarilal Nanda) Prime Minister of independent India and a significant figure in the Indian independence movement. Following India?s independence, Shastri was appointed Parliamentary Secretary in his home state, Uttar Pradesh. He became the Minister of Police and Transport Minister, he was the first to appoint women conductors. As the minister in charge of the police Department, he ordered that Police use jets of water instead of lathis to disperse unruly crowds. In 1951, he was made the General Secretary of the All-India Congress Committee, with Jawaharlala Nehru as the president. He was directly responsible for the selection of candidates and direction of publicity and election activities. He played an important role in the land slide successes of congress party in the Indian general election of 1952, 1957 and 1962.
Keywords: Freedom Fighter India